Economic Value of Education in Gender Perspective: Regression Analysis of Women's Perceptions in Yogyakarta City - Darini, Darini; Rachmawatie, Dessy; Maruf, Ahmad (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study examines the economic value of education from a gender perspective by analyzing women’s perceptions in Yogyakarta City. It aims to identify the influence of experiences and information related to female education, perceptions of gender roles in economic participation, and perceptions of environmental support on the perceived economic value of education. A quantitative approach was employed using survey data collected from women respondents, analyzed through multiple linear regression. The results indicate that all variables have a positive and statistically significant effect on the perceived economic value of education. Experiences and information regarding female education are the most influential factors, followed by perceptions of gender roles and environmental support. Simultaneously, these variables explain a substantial proportion of the variation in women’s perceptions. The study concludes that the economic value of education for women is shaped by the interaction of personal experiences, social norms, and environmental support, highlighting the importance of integrated efforts to enhance the economic relevance of education for women.